Gender and Class in Modern Europe - Rose, Sonya O.; Frader, Laura Levine, 1945- (Book collections on Project MUSE., 1996)
Gender figured significantly in the industrial, social, and political transformations of the United Kingdom and Ireland, France, Germany, and Russia. This book explores its importance during a period of radical change for the working classes, from 1800 through the 1930s. Collectively, the authors demonstrate how the study of gender can lead to a new understanding of working class history. The authors-leading historians, sociologists, and feminist scholars ask how gender meanings and relations shaped and were shaped by transformations in areas ranging from the Irish linen industry to German social policy, from the French labor movement to Britain's interracial settlements. With special attention to the importance of language and culture in social life, they show how political identities are constituted and social categories created, contested, and changed-and how gender plays a central role in this process. Contributors: Kathleen Canning, University of Michigan; Helen Harden Chenut, Centre National de la Recherche Scientifique, Paris; Anna Clark, University of North Carolina, Charlotte; Judy Coffin, University of Texas, Austin; Jane Gray, St. Patrick's College, Maynooth, Republic ofireland; Tessie P. Llu, Northwestern University; Judith F. Stone, Western Michigan University; Laura Tabili, University of Arizona; Eric D. Weitz, St. Olaf College; Elizabeth A. Wood, Massachusetts Institute of Technology.